RZYMSKA TERMINOLOGIA STOSOWANA NA OKREŚLENIE NARZĘDZI UŻYWANYCH PODCZAS CHŁOSTY - Kołodko, Piotr (Zeszyty Prawnicze, 2017)
The Roman Terminology Applied to Define Tools Used for Flogging Summary It can be taken for granted that the Roman law knew several tools which were used for flogging (e. g. verber, virga, vitis, flagellum, fustis, ferula, plumbata). Their choice was determined by the personal status of the wrongdoer on whom flogging was inflicted (distinction between humiliores-honestiores, servi). Thus, servi were flogged with verber or flagellum whilst humiliores were beaten with fustis (the same instrument as long as vitis were applied to the soldiers - milites). Those Romans who were called honestiores were excluded from flogging (as an additional punishment), at least from the time of principate. The severity of flogging was connected with the kind of an instrument which was applied. Hence, the most severe flogging was when plumbata was used, because of its construction (plumbata had tips finished with leaded balls). This instrument (as well as verber) was applied when a delinquent was tortured. It seems that Roman law did not treat all those mentioned instruments for flogging as equivalent. Although the lexical meaning of e. g. verber or virga is similar there is a significant difference between them, which is related to personal status of delinquents on whom flogging was inflicted.